Clinical Impact of Staphylococcus aureus Skin and Soft Tissue Infections - Matthew S. Linz; Arun Mattappallil; Diana Finkel; Dane Parker (MDPI AG, 2023)
The pathogenic bacterium Staphylococcus aureus is the most common pathogen isolated in skin-and-soft-tissue infections (SSTIs) in the United States. Most S. aureus SSTIs are caused by the epidemic clone USA300 in the USA. These infections can be serious; in 2019, SSTIs with S. aureus were associated with an all-cause, age-standardized mortality rate of 0.5 globally. Clinical presentations of S. aureus SSTIs vary from superficial infections with local symptoms to monomicrobial necrotizing fasciitis, which can cause systemic manifestations and may lead to serious complications or death. In order to cause skin infections, S. aureus employs a host of virulence factors including cytolytic proteins, superantigenic factors, cell wall-anchored proteins, and molecules used for immune evasion. The immune response to S. aureus SSTIs involves initial responders such as keratinocytes and neutrophils, which are supported by dendritic cells and T-lymphocytes later during infection. Treatment for S. aureus SSTIs is usually oral therapy, with parenteral therapy reserved for severe presentations; it ranges from cephalosporins and penicillin agents such as oxacillin, which is generally used for methicillin-sensitive S. aureus (MSSA), to vancomycin for methicillin-resistant S. aureus (MRSA). Treatment challenges include adverse effects, risk for Clostridioides difficile infection, and potential for antibiotic resistance.